2007
DOI: 10.3892/ijmm.19.1.197
|View full text |Cite
|
Sign up to set email alerts
|

WNT antagonist, DKK2, is a Notch signaling target in intestinal stem cells: Augmentation of a negative regulation system for canonical WNT signaling pathway by the Notch-DKK2 signaling loop in primates

Abstract: Abstract. Notch and WNT signaling pathways are key components of the stem cell signaling network. Canonical WNT signaling to intestinal progenitor cells leads to transcriptional activation of the JAG1 gene, encoding Serratetype Notch ligand. JAG1 then binds to the Notch receptor on adjacent stem cells to induce Notch receptor proteolyses for the release of Notch intracellular domain (NICD). NICD is associated with CSL/RBPSUH and Mastermind (MAML1, MAML2, or MAML3) to activate Notch target genes, such as HES1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 34 publications
(40 reference statements)
0
25
0
Order By: Relevance
“…2). Interestingly, endothelial cell-specific Dkk-2 Tg mice display a vascular phenotype similar to Jag-1 Tg mice (74), and Jag-1 promotes Dkk-2 expression through Notch in human small intestine stem cells (75). These results imply that Dkk-2 might regulate angiogenic activity of endothelial cells through crosstalk with Notch signaling.…”
Section: Dickkopf-2mentioning
confidence: 85%
“…2). Interestingly, endothelial cell-specific Dkk-2 Tg mice display a vascular phenotype similar to Jag-1 Tg mice (74), and Jag-1 promotes Dkk-2 expression through Notch in human small intestine stem cells (75). These results imply that Dkk-2 might regulate angiogenic activity of endothelial cells through crosstalk with Notch signaling.…”
Section: Dickkopf-2mentioning
confidence: 85%
“…Recent in silico analysis suggested that DKK2 is a Notch signaling target in intestinal stem cells (33). However, Notch-response elements were detected in the promoter region of DKK2 of human, chimpanzee, and rat, but not in cow and mouse (33). Thus, it remains unclear whether angiogenic action of DKK2 is functionally correlated with Notch signaling.…”
Section: Figurementioning
confidence: 95%
“…Thus, the expression pattern and Tg phenotypes point to a potential relationship between Jag1 and DKK2 in sprouting angiogenesis. Recent in silico analysis suggested that DKK2 is a Notch signaling target in intestinal stem cells (33). However, Notch-response elements were detected in the promoter region of DKK2 of human, chimpanzee, and rat, but not in cow and mouse (33).…”
Section: Figurementioning
confidence: 99%
“…Exonintron boundaries were determined based on the consensus sequence of exon-intron junctions ('gt ..... ag' rule of intronic sequence) and codon usage within the coding region. Conserved transcription factor-binding sites within promoter regions were then searched for based on the Match program, Genetyx program, and manual curation as previously described (43)(44)(45) In silico expression analyses. Expressed sequence tags (ESTs) derived from human HES/HEY family members were searched for using the BLAST programs as previously described (48)(49)(50) …”
Section: Methodsmentioning
confidence: 99%